2009
DOI: 10.1111/j.1600-0854.2009.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding Site Distribution of Nuclear Transport Receptors and Transport Complexes in Single Nuclear Pore Complexes

Abstract: Transport through the nuclear pore complex (NPC) involves a large channel and an abundance of binding sites for nuclear transport receptors (NTRs). However, the mechanistically important distribution of NTRbinding sites along the channel is vividly debated. In this study, we visualized binding site distributions directly by two complementary optical super-resolution methods, single-molecule microscopy and 4Pi microscopy. First, we analyzed the distribution of RanGDP because this important nuclear transport sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The spatial location of cargo–receptor dissociation remains unclear 50 . The distribution of Ran and an importin-β1 truncation with reduced binding affinity for Ran did not indicate a clear location for the release of the receptor–cargo complex 19,36 . For import factors and cargoes, most data indicate that the binding-site distribution along the nuclear–cytoplasmic axis of the central channel is symmetrical, with peaks only a few nanometres off centre compared with the POM121 marker signal (Table 1), although an exception is found for the export of messenger RNA 11 (see below).…”
Section: Transport and Single-molecule Microscopymentioning
confidence: 86%
See 1 more Smart Citation
“…The spatial location of cargo–receptor dissociation remains unclear 50 . The distribution of Ran and an importin-β1 truncation with reduced binding affinity for Ran did not indicate a clear location for the release of the receptor–cargo complex 19,36 . For import factors and cargoes, most data indicate that the binding-site distribution along the nuclear–cytoplasmic axis of the central channel is symmetrical, with peaks only a few nanometres off centre compared with the POM121 marker signal (Table 1), although an exception is found for the export of messenger RNA 11 (see below).…”
Section: Transport and Single-molecule Microscopymentioning
confidence: 86%
“…However, emerging single-molecule imaging approaches are showing the real-time dynamics of nuclear transport, and are illuminating its mechanism. Examples of these technologies are 4-Pi microscopy 35,36 , single point edge excitation subdiffraction microscopy 37 , fluorescence correlation spectroscopy (FCS) 21,38 , single-molecule tracking 10,19,39,40 and super-registration microscopy 11 (Box 1). The application of such approaches to determine the distribution of Nups and transport-factor-binding sites supports the notion that the NPC functionally extends far into both compartments (the nucleoplasm and cytoplasm) on either side of itself 8,11,19 .…”
Section: Transport and Single-molecule Microscopymentioning
confidence: 99%
“…The recently reported FXFG nanopore system (89) may prove a useful tool for probing the conformation and biophysical state of FG domains in the presence of transport receptors. High-resolution microscopic analysis of transport receptor binding to NPCs has recently demonstrated that transport receptors are distributed relatively uniformly along the NPC channel (90). This observation suggests that FG domains are distributed and accessible throughout the NPC, rather than predominantly directed toward the ends of the pore.…”
Section: Reconciling Differences Between Modelsmentioning
confidence: 89%
“…This observation suggests that FG domains are distributed and accessible throughout the NPC, rather than predominantly directed toward the ends of the pore. Continued experiments using these advances in microscopy (90) and artificial selective nanopores (89) have the potential to provide further insights into the NPC gating and translocation mechanism.…”
Section: Reconciling Differences Between Modelsmentioning
confidence: 99%
“…The SPEED approach yields 0.4 ms time resolution and 10 nm static spatial precision [56], yielding an accuracy of ~20 nm for mobile particles [50]. 4Pi microscopy also provides ~10 nm static spatial resolution, but does not yet have single molecule sensitivity [69]. A static precision of 6 nm has been obtained with nuclear-targeted quantum dots [70].…”
Section: Single Molecule Fluorescence Approachesmentioning
confidence: 99%